Validation and Psychometric Properties of the Chinese Version of the Fear of Missing Out Scale - Li, Yan-Yu; Huang, Yi-Ting; Dou, Kai (International journal of environmental research and public health, 2021)
Objectives: The present study aimed to examine the psychometric properties of Przybylski’s 10-item Fear of Missing Out scale and to investigate the measurement invariance across age and gender among Chinese adolescents and emerging adults. Methods: A convenient sample of 2886 subjects (Mage = 14.79, SD = 4.03; 47.96% male) was recruited in south China. Item analysis, EFA, CFA, testing of measurement invariance across gender and age, reliability analysis, and concurrent validity analysis were conducted. A subsample of 154 subjects (Mage = 15.3, SD = 2.22; 54% male) completed the scale again after 6 months to assess the test–retest reliability. Results: The EFA strongly indicated a two-dimensional solution, including fear of missing novel information and fear of missing social opportunities, for the Chinese version of the FoMO scale, which the CFA confirmed. Adequate internal consistency was found. Concurrent validity and discriminant validity were also demonstrated. Conclusions: Based on the results, the Chinese version of the FoMO scale is suitable for use among young Chinese people.